Does Auditor Industry Specialization Improve Audit Quality? - MINUTTI‐MEZA, MIGUEL (Journal of Accounting Research, 2013)
ABSTRACT This study examines whether auditor industry specialization, measured using the auditor's within‐industry market share, improves audit quality and results in a fee premium. After matching clients of specialist and nonspecialist auditors on a number of dimensions, as well as only on industry and size, there is no evidence of differences in commonly used audit‐quality proxies between these two groups of auditors. Moreover, there is no consistent evidence of a specialist fee premium. The matched sample results are confirmed by including client fixed effects in the main models, examining a sample of clients that switched auditors, and using an alternative proxy that aims to capture the auditor's industry knowledge. The combined evidence in this study suggests that the auditor's within‐industry market share is not a reliable indicator of audit quality. Nevertheless, these findings do not imply that industry knowledge is not important for auditors, but that the methodology used in extant archival studies to examine this issue does not fully parse out the effects of auditor industry specialization from client characteristics.